(untitled) (Bangladesh Rice Journal, 2025)
Bangladesh is a country with extreme weather conditions that is being investigated for its climatic effects on the production of rice (Oryza sativa L.) crops. Rice is cultivated as Aus, Aman, or Boro throughout the year in Bangladesh. The study was intended to explore the effects of climatic variables (rainfall, minimum temperature, and relative humidity) on Aus rice production in Bangladesh. Time series data of production, rainfall, minimum temperature, and relative humidity for the last decade (2011-2020) were collected from BBS (Bangladesh Bureau of Statistics), BRRI (Bangladesh Rice Research Institute), and BMD (Bangladesh Meteorological Department) to carry out the study. To make the research more specific and clear, the country was divided into four regions: the North- East, the North- West, the South-East, and the South-West. GIS (Geographic Information System) tools was used for prepare climatic mapping. The results show that rainfall and relative humidity had a significant impact on the production of Aus rice in the North-Eastern and North-Western regions, but rainfall was more effective than relative humidity in the North-Western part. Minimum temperature and relative humidity were the dominant variables in both the South-Eastern and the South-Western regions for Aus production. Bangladesh Rice J. 27(2): 83-103, 2023